Fast Neutron Irradiation Effects on (Bi1.6Pb0.4)Sr2Ca2Cu3O10 Superconductor Prepared Using Co-precipitation Technique - Mujaini M.; Ilhamsyah A.B.P.; Muhammad-Najib K.; Hamid N.A.; Awang R.; Omar F.S.; Idris F.M.; Bayar A.M.J.; Abd-Shukor R. (Springer, 2024)
Neutron irradiation is one of the methods to improve the transport properties of superconductors by creating defects for flux pinning centers. In this work, the effects of fast neutron irradiation on (Bi1.6Pb0.4)Sr2Ca2Cu3O10 (Bi-2223) superconductor were studied. The samples were prepared using the co-precipitation technique and were exposed to fast neutron irradiation via pneumatic transfer system (PTS) with a neutron flux of 2.5 1012 n cm?2s?1 from 60 to 660s which are equivalent to neutron fluences of 1.55 1014 to 1.70 1015 n cm?2. The non-irradiated sample was dominantly Bi-2223 phase (85%) as shown by X-ray diffraction patterns. However, after irradiation, the volume fraction of the Bi-2223 was reduced and the (Bi1.6Pb0.4)Sr2CaCu2O8 (Bi-2212) phase increased, resulting in an almost 50:50 ratio of Bi-2223:Bi-2212. Energy-dispersive X-ray analysis indicated the presence of Zn and Po in some irradiated samples due to neutron activation. The onset transition temperature (Tc-onset) and zero transition temperature (Tc-zero) for the non-irradiated sample was 118K and 105K, respectively. The irradiated samples showed lower Tc-onset (112 to 115K) and Tc-zero (100 to 104K). AC susceptibility showed a transition temperature (Tc??) around 108 to 109K. The imaginary part of the susceptibility showed intergranular loss peak temperature (Tp) from 89 to 96K. Intermediate fluence of fast neutron irradiation did not affect the intergrain coupling and pinning strength of (Bi1.6Pb0.4)Sr2Ca2Cu3O10. However, higher fluence severely damaged the microstructure and degraded the flux pinning strength of (Bi1.6Pb0.4)Sr2Ca2Cu3O10. 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.